Penggunaan Bahasa Indonesia Pada Penulisan Media Ruang Publik Di Kota Cirebon - Fauziyah, Salma; Adiman, Salsabila Arti; Kusmana, Suherli (Jurnal Ilmiah Wahana Pendidikan, 2026)
focusing on spelling accuracy, standard vocabulary selection, and sentence structure effectiveness, as well as analyzing public responses to the readability and comprehensibility of the language used. The method used is descriptive qualitative with data collection techniques through observation and interviews. The results of the study show that there are still various linguistic inaccuracies such as spelling errors, the use of foreign loanwords, ineffective sentences, and non-standard abbreviations. Public responses also vary, with some being tolerant as long as the meaning can be understood, while others feel disturbed. These findings emphasize that the functionality of language in public spaces is not solely determined by standardization but also by the effectiveness of communication and social context. Therefore, collective awareness is needed in the proper use of the Indonesian language to support clear and meaningful communication.